2004
DOI: 10.1111/j.1651-2227.2004.tb03027.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and significance of minor anomalies in children with impaired development

Abstract: The high prevalence of multiple minor anomalies in children with developmental disorders suggests that during early development, factors which cause the specific developmental disorder and the occurrence of a minor anomaly have a joint effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The prevalence of CP in our study was found as a 17.9% rate, which was similar to this finding. It was reported that in 10-15% of cases with MR have visual impairments and 10-15% have hearing problems [13]. Similar with these reports, in our study we found that speaking and/or hearing impairment was 9.4% of the cases.…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of CP in our study was found as a 17.9% rate, which was similar to this finding. It was reported that in 10-15% of cases with MR have visual impairments and 10-15% have hearing problems [13]. Similar with these reports, in our study we found that speaking and/or hearing impairment was 9.4% of the cases.…”
Section: Discussionsupporting
confidence: 82%
“…The incidence of minor physical anomalies has also been studied in search of relationships between various non‐syndromic disorders and abnormal embryogenesis or phenogenesis. Well‐known examples are the studies in childhood cancer [Kobayashi et al, 1968; Stojimirovic, 1981; Méhes et al, 1985, 1994, 1998; Fékété et al, 1987; Roganovic et al, 2002; Merks et al, 2003], diabetes mellitus [Méhes et al, 1986], metabolic disorders [Méhes, 1991], isolated urinary tract malformations [Méhes and Pinter, 1990], mental retardation [Smith and Bostian, 1964; Firestone et al, 1978; Meggyessy et al, 1980; Coorssen et al, 1991; Ulovec et al, 2004; Van Karnebeek et al, 2005], cerebral palsy [Miller, 1989], hyperactivity [Waldrop et al, 1968, 1978; Waldrop and Goering, 1971; Quinn and Rapoport, 1974; Walker, 1977; Campbell et al, 1978; Firestone et al, 1978; Burg et al, 1980; Links, 1980; Links et al, 1980; Simonds and Aston, 1981; Gualtieri et al, 1982; Vanoverloop et al, 1982; Fogel et al, 1985; Accardo et al, 1991], autism [Steg and Rapoport, 1975; Rodier et al, 1997; Miles and Hillman, 2000; Van Karnebeek et al, 2002], and other psychiatric disorders [Steg and Rapoport, 1975; Guy et al, 1983; Green et al, 1987, 1989, 1994a,b; O'Callaghan et al, 1991, 1995; McNeil et al, 1992; Lohr and Flynn, 1993; Alexander et al, 1994; McGrath et al, 1995, 2002; Lane et al, 1997; Lohr et al, 1997; Trixler et al, 1997, 2001; Akabaliev and Sivkov, 1998; Griffiths et al, 1998; Ismail et al, 1998, 2000; Weinstein et al, 1999; Akabaliev et al, 2001; Lawrie et al, 2001; Scutt et al, 2001; Schiffman et al, 2002; Elizarraras‐Rivas et al,…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of an identifiable syndrome, an increase in MPAs has also been reported in several groups including newborns, school-aged children, schizophrenic and autistic individuals, mentally retarded children, psychoneurotic children learning-disabled children speech, language and hearing-impaired children, hyperactive children and inhibited children. 6,8,9,11,13,16,[16][17][18][19][21][22][23][24][25][28][29][30][31][32][33] The previous literature described wide differences in the average frequency of MPAs per child among healthy school children. Steg et al, found an average value of 2.88, while Firestone et al, found 1.4 minor anomalies per child, for boys.…”
Section: Discussionmentioning
confidence: 99%
“…Various literature published in the past has concentrated on the prevalence, association and/or correlation of the MPAs in various psychiatric disorders like schizophrenia, attention-deficit hyperkinetic disorder (ADHD), first episode psychosis etc. 6,[13][14][15][16][17][18] There are only few studies in world literature where prevalence of MPAs has been assessed in children with mental impairment. 8,16,17 To our knowledge this is the first Indian study where prevalence of MPAs is being assessed in mentally retarded children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation